Penawaran Proyek Kontinum Publikasi Artikel Ilmiah Mahasiswa - Fitriani Fitriani; Susanti Vera; Putri Anditasari; Hidayatul Fikra (UIN Sunan Gunung Djati Bandung, 2024)
This article aims to present a continuum project offering for student scientific article writing. This article uses a qualitative approach by applying descriptive methods. The results of the discussion of this article show that the implementation of a continuum project can involve a number of agreements between users and organizers in ensuring the successful publication of student scientific articles in standard journals. This article concludes that continuum project bidding can be continued at the contract stage with academic institutions, especially higher education institutions in Indonesia.